1985
DOI: 10.1007/bf02215146
|View full text |Cite
|
Sign up to set email alerts
|

Faecal bacteria of wild ruminants and the alpine marmot

Abstract: Faecal samples from 60 red deer (Cervus elaphus), 13 roe deer (Capreolus capreolus), 7 chamois (Rupicapra rupicapra), 41 alpine marmot (Marmota marmota) and soils mixed with deer faeces from the Stelvio National Park were examined for Campylobacter sp. and Salmonella sp. with negative results. The same material, especially deer faeces, was a habitat highly suitable for Yersinia sp.: Y. enterocolitica (two biotypes) was isolated twice, Y. kristensenii (two serotypes) was isolated 19 times, Y. frederiksenii and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In a study in Poland, it was confirmed that red deer and roe deer were carriers of Listeria and Campylobacter (Koronkiewicz, et al 2004). Several studies indicate that wild ruminants are a major reservoir of Yersinia (Shayegani 1983, Henderson 1984, Pagano, et al 1985.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in Poland, it was confirmed that red deer and roe deer were carriers of Listeria and Campylobacter (Koronkiewicz, et al 2004). Several studies indicate that wild ruminants are a major reservoir of Yersinia (Shayegani 1983, Henderson 1984, Pagano, et al 1985.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous attempts to identify Salmonella spp. in feces from healthy cervid populations have not been successful (Henderson and Hemmingsen, 1983;Pagano et al, 1985;Wahlstrom et al, 2003;Branham et al, 2005). Estimating the prevalence and serovars of Salmonella in deer populations will aid in determining the potential impact on domestic and wild animal populations and the risk of human disease from Salmonella shed in the feces of deer.…”
mentioning
confidence: 99%
“…Previous surveys of clinically normal cervid populations failed to identify Salmonella spp. in fecal samples from 122 deer farms (3,810 samples) in New Zealand (Henderson and Hemmingsen, 1983), 60 red deer and 13 roe deer in Italy (Pagano et al, 1985), 86 moose, 172 roe deer, and 37 red and fallow deer in Sweden (Wahlstrom et al, 2003), or 26 white-tailed deer harvested by hunters in Texas, USA (Branham et al, 2005). Salmonella were detected in 2 (8%) of 26 samples that were collected from the rumen of white-tailed deer harvested on a university ranch in Texas, USA (Branham et al, 2005).…”
mentioning
confidence: 99%
“…Unfortunately, the samples for bacteriological investigations were pooled by the authors what obscures the picture of current situation concerning Y. enterocolitica infections in this animal species. Pagano et al (1985) conducted one of the first studies on the prevalence of Yersinia spp. in wild animals in Europe.…”
Section: Discussionmentioning
confidence: 99%